2001
DOI: 10.1073/pnas.151261398
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral anti-Aβ antibody alters CNS and plasma Aβ clearance and decreases brain Aβ burden in a mouse model of Alzheimer's disease

Abstract: Active immunization with the amyloid ␤ (A␤) peptide has been shown to decrease brain A␤ deposition in transgenic mouse models of Alzheimer's disease and certain peripherally administered anti-A␤ antibodies were shown to mimic this effect. In exploring factors that alter A␤ metabolism and clearance, we found that a monoclonal antibody (m266) directed against the central domain of A␤ was able to bind and completely sequester plasma A␤. Peripheral administration of m266 to PDAPP transgenic mice, in which A␤ is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,032
4
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,222 publications
(1,103 citation statements)
references
References 37 publications
51
1,032
4
9
Order By: Relevance
“…59 The second hypothesis did not rely on anti-Ab antibodies crossing the blood brain barrier. Rather, the "peripheral sink hypothesis" proposed by DeMattos et al [72][73][74] involved the sequestering of Ab in an immune complex in the blood, thereby lowering the level of free Ab, which contributed to a net efflux of Ab from the brain. They also suggested that therapeutically relevant concentrations of antiAb antibodies do not cross the blood brain barrier (BBB), as suggested by the theoretical calculations of the levels of both anti-Ab antibodies and Ab in the serum and CNS.…”
Section: Discussionmentioning
confidence: 99%
“…59 The second hypothesis did not rely on anti-Ab antibodies crossing the blood brain barrier. Rather, the "peripheral sink hypothesis" proposed by DeMattos et al [72][73][74] involved the sequestering of Ab in an immune complex in the blood, thereby lowering the level of free Ab, which contributed to a net efflux of Ab from the brain. They also suggested that therapeutically relevant concentrations of antiAb antibodies do not cross the blood brain barrier (BBB), as suggested by the theoretical calculations of the levels of both anti-Ab antibodies and Ab in the serum and CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the N-terminus of the immunodominant B cell epitope of Aβ [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] was synthesized in tandem with a promiscuous foreign T cell epitope, PADRE (aK-Cha-VAAWTLKAAa, where "a" is D alanine and "Cha" is L-cyclohexylalanine) as Multiple Antigenic Peptides (MAP), which contain a core matrix of 4 branching lysines [42,43] to generate PADRE-Aβ 1-15 -MAP molecules (Invitrogen Inc., CA).…”
Section: Epitope Vaccine Peptide and Immunizationsmentioning
confidence: 99%
“…One potentially powerful strategy for reducing the level of Aβ in the brain is immunotherapy, in which antibodies specific to Aβ facilitate the clearance of amyloid deposits [10][11][12][13][14][15][16][17][18]. The first human AD vaccine consisted of fibrillar Aβ 42 formulated in QS21 adjuvant (AN-1792 trial) that induced strong Th1-type anti-Aβ immune responses [19], even in Th2-prone BALB/c mice [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was extended to the PDAPP strain of mice by Dodart and colleagues [50]. This group previously reported that chronic treatment of PDAPP mice with the m266 anti-Aβ antibody (every 2 weeks from 4 to 9 months of age) reduced Aβ burden at least in part by increasing peripheral clearance [55]. In the subsequent study in 24 month-old PDAPP mice [50], they found that a "subchronic" six-week course of m266 immunotherapy reversed the cognitive deficits measured, but did not decrease the Aβ immunohistochemical burden (brain Aβ levels were not determined by ELISA).…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 79%